Symptomatic aneurysm of ductus arteriosus in neonates - Nageswara R Koneti; Vasudevan Kanchi; Hemasree Kandraju; S Jaishankar (Wolters Kluwer Medknow Publications, 2011)
Four neonates presented within 24 hours of birth with stridor, respiratory distress and a weak cry. Clinical examination of the cardiovascular system revealed no abnormality. The transthoracic echocardiogram showed large aneurysm of ductus arteriosus at the aortic isthmus, tapering to a small tortuous channel at the site of pulmonary artery insertion. Computerized tomography scan performed in two of the neonates demonstrated considerable compression of adjacent thoracic structures. One required surgical excision due to persistence of symptoms. Serial echocardiograms in the remaining three babies showed transition through various stages of resolution over a period of 6 weeks to 3 months, resulting in the obliteration of the aneurysm. All babies are doing well during the follow-up.